Chitinase and Peroxidase Activities, Stomatal Density and Resistance of CocoaAgainst Black Pod Disease - Rubiyo Rubiyo; Agus Purwantara; Sudarsono Sudarsono (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2010)
Research based on morphology which is related to structural resistance such as stomata density and chemical resistance involving chitinase and peroxidase enzymes needs to be conducted. Hereafter, cacao resistant mechanism against Phytophthora palmivora can be realized. Research took place in June 2008 till February 2009 in Plant Disease Laboratory and Experiment Station of Kaliwining, Indonesian Coffee and Cacao Research Institute, Jember, East Java. Research on chitinase and perxidase analysis took place in Inter University Center Laboratory of Bogor Agriculture University (IPB). Based on stomata observation of 10 clones, the stomata density in pod and leaf did not give high correlation to the resistance. Resistant cacao clone did not always low stomata density compared to susceptible ones. Cacao clone which was susceptible did not always have high stomata density in pod and leaf. The number of stomata did not give significant difference between resistant clones and susceptible ones. The activities of chitinase and peroxidase enzymes upon tested clones indicated that there was chitinase role in the resistance of cacao against the infection by P. palmivora fungi. The increase of chitinase activity fungus in resistant clones generally intensified consistently, and similiar with peroxidase enzyme.Key words: Chitinase activity, peroxidase, stomata, Phytophthora palmivora, cacao resistance.